Tantangan Globalisasi dan Strategi Ketahanan Ekonomi Domestik di Era Perdagangan Bebas - Ahmad Ramadhan (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
This article examines the challenges posed by globalization and the strategies required to strengthen domestic economic resilience in the era of free trade. The research aims to analyze how globalization impacts national economies, particularly in developing countries, and to propose strategies that can enhance their competitiveness while maintaining economic sovereignty. Using a qualitative research design, this study relies on secondary data from journals, policy reports, and economic statistics. The results indicate that globalization provides opportunities in terms of market access, investment, and technology transfer, but simultaneously creates threats such as market dependency, trade deficits, and deindustrialization. The discussion emphasizes the need for adaptive policies, investment in human capital, strengthening local industries, and enhancing regional economic cooperation. This study concludes that a balance between global integration and domestic resilience is crucial for sustainable economic development. Recommendations include fostering innovation, building institutional capacity, and encouraging inclusive policies that reduce inequality. These findings contribute to the ongoing debate on globalization and provide insights for policymakers aiming to safeguard national economic interests.